Self Rated Health among Syrian refugees in Lebanon and Norway – a cross sectional study. (13th November 2019) - Haj-Younes, J; Strømme, E M; Hasha, W; Abildsnes, E; Fadnes, L T; Kumar, B; Diaz, E
Abstract: Background: Refugees are often exposed to various stressors before, during and after migration that can cause adverse health effects. Prior research indicates that the health status of refugees is a significant factor in determining their success in resettlement. This study aims to assess self-rated health (SRH) and factors associated with SRH among Syrian refugees in Lebanon and Norway. Methods: The study uses a cross-sectional design with data from a self-administered survey among 827 adult Syrian asylum seekers of whom 506 were recruited in Lebanon, and 321 in Norway. Inclusion criteria were subjects who self-identified as Syrian nationals above the age of 16. The survey was conducted in 2017 and 2018 in collaboration with International Organization of Migration in Lebanon and through mandatory educational activities in Norway. Data analysis was performed for the main outcome self-rated health (SRH), a validated health status indicator, which was dichotomized into "good" and "poor" SRH. Odds Ratios for poor SRH were estimated adjusting for age, gender and country of residence. Results: A total of 827 of 972 (85%) who were invited answered the questionnaire. The mean age was 33 years and 74% were men. Factors associated with good SRH were being Kurdish (AOR: 0.48 (0.23 to 0.97)) compared to Arabic ethnicity, being married (AOR 0.54 (0.29 to 0.99)) compared to being single, migrating alone (AOR 0.59 (0.37 to 0.96)) compared to co-migration and having low health literacy level (AOR: 0.64 (0.42 to 0.93)). In contrast, poor SRH was significantly increased with long time in transit country/ies (AOR 1.49 (1.07 to 2.06)) and with older age (age 30-34 AOR 3.2, age 35-39 AOR 2.2, age 40 + AOR 2.6) compared to age group 16-24. Conclusions: Older refugees and those who stay long time in transit are at great risk of reporting poor SRH. Some of the factors associated with better health, like Kurdish ethnicity, low health literacy or migrating alone, deserve further research. Key messages: Age and long stay in transit is associated with poor SRH among Syrian refugees. Demographic background and migrant related factors should be taken into account when planning refugee resettlement and healthcare provision.